Prevalence of Human papillomavirus among women following HPV vaccine introduction; a systematic review - Muusha, Prudence (Department of Public Health and Family Medicine, 2019)
Background: Worldwide efforts have been made by some countries to offer HPV vaccination since its introduction in 2006. Population effectiveness of HPV vaccines is presently an active area of research. We review available evidence on the effectiveness of HPV vaccine uptake among female adolescents to prevent HPV infection. Methods: A comprehensive search of published and grey literature was conducted in several electronic databases using a pre-defined search strategy related to HPV prevalence following vaccination. The database searches were complemented by hand-searches of reference lists of eligible studies. Data were extracted onto a purpose-designed data extraction form, pooled in a meta-analysis and stratified by continent considering vaccine type, cross protective and (high/low) risk HPV types as subgroups. Results: Our search yielded 1680 studies, of which thirteen met with our inclusion criteria (8332 vaccinated women aged 12 to 34 years from across the world). The pooled HPV (comprising types 6, 11, 16 and 18) prevalence among vaccinated female adolescents was 7% (95% Confidence Interval (CI): 5% to 9%, 13 studies, n=8,332). The 13 studies were conducted across 3 continents: HPV prevalence for North America was 5% (95% CI: 3% to 7%, 9 studies, n=5781, age range =13 to 34); Europe, 14% (95% CI: 9% to 18%, 3 studies, n=2213, age range =13 to 29) and Australia 5% (95% CI: 3% to 8%, 1 study, n=5781, age range=13 to 34). Of the studies which reported the effect of vaccination on other non-vaccine HPV type prevalence (known as cross protective types) HPV (31, 33, 45, 51 & 58), the overall pooled cross protective HPV prevalence was 9% (95% CI: 6% to 12%, 4 studies, n=3081 age range=13 to 29), by continent North America had 14% (95% CI: 12 to 17%, 1 study, n=753 age range=14 to 24), Europe 7% (95% CI: 6 to 8%, 2 studies, n=1990, age range=13 to 29) and Australia with 8% (95% CI: 5% to 11%, 1 study, n=338 age range=18 to 26). Conclusion: This study showed an HPV prevalence of 7% in women vaccinated against HPV types 6,11,16 and 18, which represents a substantial difference to the 22% HPV prevalence in non-vaccinated women. There was no statistically significant difference between HPV prevalence across the continents. There is however, still a dearth of information on vaccinated women and HPV prevalence, highlighting the need for further studies in this area. Strengths and limitation of this review • The review comprehensively searched multiple databases and bibliographies. We had no language restrictions. • We were stringent in the selection of studies as far as vaccination status was concerned. Studies considering HPV prevalence in unvaccinated women were excluded. • A variety of methods was utilised in collecting data across the studies. However, some of the study participants were not representative of the general population. Caution therefore, needs to be considered when using these results to make inferences or conclusions about prevalence of certain populations.